A center of a polytope: An expository review and a parallel implementation - S. K. Sen; Hongwei Du; D. W. Fausett (International Journal of Mathematics and Mathematical Sciences)
The solution space of the rectangular linear system Ax=b, subject to x≥0, is called a polytope. An attempt is made to provide a deeper geometric insight, with numerical examples, into the condensed paper by Lord, et al. [1], that presents an algorithm to compute a center of a polytope. The algorithm is readily adopted for either sequential or parallel computer implementation. The computed center provides an initial feasible solution (interior point) of a linear programming problem.